Hubungan antara Menopause Dengan Hipertensi di Puskesmas Penumping Surakarta - Dendy Raharjo; Yoseph Indrayanto; Slamet Riyadi (Nexus Kedokteran Komunitas, 2013)
Background:Hypertension is here defined as systolic arterial blood pressure at least 140 mmHg or diastolic arterial blood pressure at least 90 mmHg or taking anti-hypertensive drugs. Onset varietyof hypertension is influenced by various factors, one of which is menopause. In this study,sample data of menopausewas obtained by using questionnaire sheet. The purpose of this study is to determine the relationship between menopause and hypertension. Methods:This study is an observational analysis with cross sectional study approach. The sampling technique employed was purposive sampling. Sample size comprises 47 female patients. The research was conducted in July 2013 at Penumping Community Health Center, Surakarta. Data was obtained by questionnaire and direct measurement of the weight and height. The statistical analysis used was Chi-Square. Results:Chi-Square analysis results obtained p = 0.046 (p <0.05). This analysis showed significant association between menopause and hypertension in Penumping Community Health Center Surakarta. Conclusions:Based on this study it can be concluded that there is a positive relationship between menopause and hypertension. Keywords:menopause , hypertension